Commitment, enjoyment and motivation in young soccer competitive players - Garcia-Mas, Alexandre (2013)
Building upon Deci’s and Ryan (1985) Self-determination theory as well as the sportive behavioral correlates of the model of Commitment (Scanlan et al., 1976), this study tries to establish the relationship between motivation and commitment in youth sport. For this purpose 454 young competitive soccer players answered the Sport Motivation Scale (SMS) and the Sport Commitment Questionnaire (SCQ) during the regular season. The SMS measures the three dimensions of the Motivational continuum (the Amotivation, the Extrinsic Motivation and the Intrinsic Motivation). The SCQ measures the Sportive Commitment and its composing factors such as the Enjoyment, the Alternatives to the sport, and the Social Pressure. Our findings provided a clear pattern of the influence of motivation in sport enjoyment and commitment, outlining the positive contribution of intrinsic and extrinsic motivation to enjoyment and commitment. Amotivation, contributes positively to alternatives to sport and negatively to enjoyment and commitment. It should be noted that extrinsic motivation has a higher contribution to enjoyment whereas intrinsic motivation has a higher contribution to commitment.